Famous Last Words: Caesar's Prophecy on the Ides of March*. (8th February 2017) - Ziogas, Ioannis
Abstract: Shakespeare's Et tu, Brute has been influential in shaping a tradition that interprets Caesar's last words as an expression of shock at Brutus' betrayal. Yet this interpretation is not suggested in the ancient sources that attest the tag καὶ σύ, τέκνον ('you too, son'). This article argues that Caesar's dictum evokes a formula of funerary epigrams, which refers to death as the common lot of all mortals. The epitaphic connotations of καὶ σύ or tu quoque feature in epic poetry, a connection that lends a Homeric dimension to Caesar's last words. The dictator's oral epitaph predicts the death of Brutus as a consequence of his involvement in the assassination. It means 'You too, son, will die'. The Greco-Roman belief that a dying man can foresee the future invests Caesar's last words with prophetic authority.